Optimalisasi Pemanfaatan Lahan Bantaran Sungai: Pengembangan Usaha Pedagang Kaki Lima (Angkringan) Melalui Inisiatif Sosial Dan Pelatihan Wirausaha - Apri Kuntariningsih; Shella Gherina Saptiany (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
This community empowerment activity aims to identify optimal use of riverbank land through developing street vendor businesses (angkringan), empowerment focusing on social initiative programs and entrepreneurial training. The methods used to empower angkringan traders include field visits (observations), focus group discussions, and outreach, the activities of which begin with an analysis of land potential along the riverbanks in Sampangan Village. The activity partners are street vendors (angkringan) located around the banks of the Sampangan river, consisting of three groups, namely a group of immigrants, a group of housewives and a group of youth who manage modern angkringan businesses. The results of empowerment for angkringan traders were identified, among others, by carrying out social initiatives, namely entrepreneurship training which covers three main aspects, including marketing, financial management and product development.